Gallium incorporation into phosphate based glasses: Bulk and thin film properties. (June 2018) - Stuart, Bryan W.; Grant, Colin A.; Stan, George E.; Popa, Adrian C.; Titman, Jeremy J.; Grant, David M.
Abstract: The osteogenic ions Ca 2+, P 5+, Mg 2+, and antimicrobial ion Ga 3+ were homogenously dispersed into a 1.45 µm thick phosphate glass coating by plasma assisted sputtering onto commercially pure grade titanium. The objective was to deliver therapeutic ions in orthopaedic/dental implants such as cementeless endoprostheses or dental screws. The hardness 4.7 GPa and elastic modulus 69.7 GPa, of the coating were comparable to plasma sprayed hydroxyapatite/dental enamel, whilst superseding femoral cortical bone. To investigate the manufacturing challenge of translation from a target to vapour condensed coating, structural/compositional properties of the target (P51MQ) were compared to the coating (P40PVD) and a melt-quenched equivalent (P40MQ). Following condensation from P51MQ to P40PVD, P2 O5 content reduced from 48.9 to 40.5 mol%. This depolymerisation and reduction in the P-O-P bridging oxygen content as determined by 31 P NMR, FTIR and Raman spectroscopy techniques was attributed to a decrease in the P2 O5 network former and increases in alkali/alkali-earth cations. P40PVD appeared denser (3.47 vs. 2.70 g cm −3 ) and more polymerised than it's compositionally equivalent P40MQ, showing that structure/ mechanical properties were affected by manufacturing route. Graphical abstract: fx1